2021
DOI: 10.1039/d1ra03560f
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of crystalline bismuth nanoparticles using lemon juice

Abstract: Lemon juice effectively served as a reducing and capping agent for an easy, cost-effective, and green synthesis of crystalline bismuth nanoparticles (BiNPs) in basic aqueous media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…We also clarified that ethanol and chloroform can partially remove the coating layer and found that these are mainly polysaccharides and fatty acid derivatives. 37 The TEM images of BiNPs synthesized using different amounts of lemon juice (Figure 5) show the presence of predominantly formed primary crystals smaller than 10 nm with some larger particles. As the amount of lemon juice increased, the number of BiNPs increased, which is attributable to the enhanced reduction with the increase of reducing species in lemon juice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also clarified that ethanol and chloroform can partially remove the coating layer and found that these are mainly polysaccharides and fatty acid derivatives. 37 The TEM images of BiNPs synthesized using different amounts of lemon juice (Figure 5) show the presence of predominantly formed primary crystals smaller than 10 nm with some larger particles. As the amount of lemon juice increased, the number of BiNPs increased, which is attributable to the enhanced reduction with the increase of reducing species in lemon juice.…”
Section: Resultsmentioning
confidence: 99%
“…36 We recently reported the first biogenic synthesis of crystalline BiNPs using lemon juice as a reducing and capping agent. 37 Lemon, which is commonly used for cooking all over the world, has been employed for the synthesis of various nanomaterials owing to the high contents of bioactive compounds like ascorbic acid, citric acid, sugars, and polyphenols serving as reducing agents. 38 Nitroaromatic compounds are widely utilized in various industries including pharmaceuticals, agricultural chemicals, and dyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of detectable peaks that appeared in the range of 1000-1400 cm −1 was considerably weaker. By contrast, the peak at 1570 cm −1 unobservable for GO is assignable to the in-plane vibration of the C=C skeleton and adsorbed phytochemicals, mainly carboxylate moieties of lemon juice [44]. These changes in FTIR spectra clearly indicate that GO was successfully reduced to rGO and higher temperatures make GO reduction more convenient.…”
Section: Characterizationmentioning
confidence: 96%
“…The huge production of lemons represents its high commercial value and consumption flow. Lemons are rich in phytochemicals including ascorbic acid, citric acid, sugars, and polyphenols [38][39][40][41] that can serve as reducing agents for the synthesis of various metal nanoparticles from their corresponding metal ions [42][43][44]. Specifically, the high contents of ascorbic and citric acids in lemons are well known, and the detail of the typical composition of lemon juice is summarized in a review by Szopa et al [45].…”
Section: Introductionmentioning
confidence: 99%